MOTIVATIONAL GROWTH OF EMPLOYEES’ PERFORMANCE - Hitka, Miloš; Sirotiakova, Maria (Ekonomika, 2009)
Establishment of the so-called employees’ positive moral belongs to the main responsibilities of human potential management. The effective behaviour of employees predicts their systematic motivation and thus the motivating process. Incorrectly planned and applied motivation programs have a negative impact on employees, they don’t motivate employees to a maximum performance. The main goal of the paper is to group employees according to their motivation needs extracted from the questionnaire and consequently to compile similarly motivated worker groups.